2014
DOI: 10.4236/aa.2014.44025
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Assisted Reproduction on Socio-Cultural Values and Social Norms

Abstract: Since the birth of the first "test tube" baby, the use of in vitro fertilization (IVF) has undergone an enormous metamorphosis. Initially designed for blocked fallopian tubes, IVF has found a number of other clinical applications over the past 40 years. However, as the science has advanced, traditional norms of conception and parenthood have been challenged and reproductive health ethics, guidelines, and law struggle to keep pace. Controversies and debates have arisen within the law, public policy, and the mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 75 publications
0
4
0
Order By: Relevance
“…These characteristics—altruism and centrality of the (male) genetic descendants—have highlighted the idea of women's sacrifice and abnegation as well as their social compromise with their biological function, making this practice, especially in its altruistic version, increasingly accepted (Rodríguez-Jaume, González-Río, and Jareño-Ruiz 2019, 308). Since the 1980s, surrogacy demand has intensified because of the biomedical advances in reproductive techniques, together with increasing rates in biological and social infertility, patterns in gay parenting, and the globalization of the reproductive industry (Lindheim et al 2014, 229–30; Berk 2015).…”
Section: Surrogate Pregnancy: a Conceptual Reviewmentioning
confidence: 99%
“…These characteristics—altruism and centrality of the (male) genetic descendants—have highlighted the idea of women's sacrifice and abnegation as well as their social compromise with their biological function, making this practice, especially in its altruistic version, increasingly accepted (Rodríguez-Jaume, González-Río, and Jareño-Ruiz 2019, 308). Since the 1980s, surrogacy demand has intensified because of the biomedical advances in reproductive techniques, together with increasing rates in biological and social infertility, patterns in gay parenting, and the globalization of the reproductive industry (Lindheim et al 2014, 229–30; Berk 2015).…”
Section: Surrogate Pregnancy: a Conceptual Reviewmentioning
confidence: 99%
“…SP is inscribed in the dynamics of a global industry, 1 which has helped to shape what has come to be known as the phenomenon of cross-border reproductive care (Lindheim et al, 2014: 229–230). In countries like the United Kingdom (Brinsden et al, 2000), Japan (Kisu et al, 2011) or France (Petitfils et al, 2017), the literature has shown how legislation is adapting to both the empirical evidence and to the debates and paradoxes that the decision entails, which, frequently, leads to cross-border reproductive journeys in an attempt to circumvent legislation that prohibits it.…”
Section: Introduction: Surrogate Pregnancy As a ‘Social Problem’mentioning
confidence: 99%
“…However, religious beliefs can also influence the types of medical treatment perceived as acceptable, raising greater ethical and moral concerns (Canzi et al, 2020; Best et al, 2019; Greil et al, 2010). Indeed, most religions discourage or even prohibit ARTs (Lindheim et al, 2014; Sallam & Sallam, 2016; Schenker, 2005) promoting other options to face infertility, such as adoption (Belanger et al, 2008; Hollingsworth, 2000; Lamb, 2008; Park & Wonch Hill, 2014; Van Laningham et al, 2012).…”
Section: Introductionmentioning
confidence: 99%